Does Today's School/Education Respond to Society's Needs and Expectations of Reality and the Future? - Alina Dworak; Agata Rzymełka-Frąckiewicz; Teresa Wilk (Ignatianum University Press, 2023)
Objectives of the research: The aim of our study was to show that education, although rooted in the past and drawing heavily from the present, especially in modern times, is focused on the upcoming future, on preparing for life in a future marked by rapid changes in the development of civilisation and the hopes, threats and challenges associated with it. Research methods: A critical analysis of scientific/research texts was carried out. A short description of the context of the issue: The everyday reality of our lives increasingly proves that there is a great need for the harmonious and comprehensive development of the personality of children and young people. Living in a world of constant re-evaluation and clearly articulated tendencies close to ethical relativism, in a world of ecological threats, chaos in the field of beauty criteria and rapidly increasing diseases of civilisation at the end of the twentieth century (no less so two decades later), people must have a clear and distinct perspective on what they should be aiming at, on which values they should base their lives and how they should live as free, rational and responsible beings (Śnieżyński, 1999, p. 27). Research findings: The modern school becomes a place of creating needs related to the future as well as a place for locating the intentional expectations of young people and their parents in relation to functioning in reality and in the future. School has become an institution that is required to prepare young people well for life/social functioning in an unknown future. Conclusions and/or recommendations: At this point, one should ask whether the institution of a modern school is able to equip a young person with everything necessary to experience success, generally speaking, so that they will not be excluded or marginalised in the global world (Rzymełka-Frąckiewicz, 2020, pp. 93-108; Rzymełka-Frąckiewicz & Wilk, 2014, pp. 83-94).